Height and Weight Characteristics of 4-7-Year-Old Kyrgyz Children: Сonstitutional, Age, and Gender Differences - Zhanybekkyzy, Kanykei; Shatmanov, Suinali; Abdurakhmanova, Chynara; Kadyr, Zholdoshev; Gulzhon, Azhibaeva (International Journal of Child Health and Nutrition, 2024)
Background: Regular monitoring of anthropometric data of children aged 4-7 years is necessary to identify deviations from the norm, develop medical programs and recommendations that meet current needs, and update physical development standards to reflect demographic and socio-cultural changes in Kyrgyzstan. Aims: The study’s purpose was to investigate the height and weight of children aged 4-7, considering the dynamics of age, body type, and gender. Methods: The physical status of 800 children aged 4-7 years was analyzed using anatomical-anthropometric and bioimpedance methods. The children who participated in the study were ethnic Kyrgyz who lived in the city of Osh and the Osh region. Result: The study revealed that children aged 4-7 years in Kyrgyzstan exhibit a diverse distribution of body types, including asthenic (15-30%), thoracic (12-23%), muscular (15-20%), digestive (15-32%), and undetermined (16-36%), with no significant predominance of any somatotype between genders. The analysis highlighted that the most common body type in the 4-5 age group was undetermined, while the digestive type prevailed at age 7. Additionally, average body weight and length demonstrated consistent growth across both genders, with boys exhibiting higher values than girls at each age. Over the developmental period, body length increased by 1.01-1.08 times in boys and 1.01-1.05 times in girls, while body weight increased by 1.12-1.21 times in boys and 1.09-1.21 times in girls, indicating a steady growth pattern regardless of somatotype. These findings underscore the importance of monitoring growth parameters in early childhood to support healthy physical development. Conclusions: The study highlights that children aged 4-7 years in Kyrgyzstan display diverse body types and consistent growth patterns in height and weight, emphasizing the need for ongoing monitoring to ensure healthy physical development.